Genital tract GBS and rate of histologic chorioamnionitis in patients with preterm premature rupture of membrane. (2nd October 2018) - Patel, Krunal; Williams, Shauna; Guirguis, George; Gittens-Williams, Lisa; Apuzzio, Joseph
Abstract: Introduction: Histologic chorioamnionitis (HC) is a common finding in the placenta from patients with preterm premature rupture of membranes (PPROM). The purpose of this study is to determine if HC differs based on the Group B streptococcus (GBS) status in patients managed expectantly with PPROM <34 weeks gestation. Methods: A retrospective study was performed of patients admitted with PPROM between 23 0/7 and 33 6/7 weeks from 2003 to 2014 at one institution. Patients were excluded if in labor, evidence of clinical chorioamnionitis, nonreassuring fetal status, multifetal gestation, HIV positive, or if GBS specimens or placental histology were not available. Placental pathology results were compared using Fisher's exact test. Results: One hundred eighty-one patients met inclusion criteria and 55 (30.3%) were GBS positive. The prevalence of HC did not differ between the GBS positive and GBS negative groups (69 versus 64.2%, respectively; p  = .62). Clinical chorioamnionitis, endomyometritis, wound infection, maternal and neonatal sepsis did not differ between the two groups. Conclusions: Vaginal–rectal colonization with GBS on admission does not appear to affect the rate of HC nor neonatal outcome in patients managed conservatively with PPROM <34 weeks gestation.